Parenting Styles of Mothers in Shaping Independence of Children with Special Needs - Musyaropah, Ulfah; Kusuma, Nurhayati Adiratna; Kurniawati; Putri, Asti Iryanti; Haibar, Rizky Allivia Larasati (Journal of Islamic Communication and Counseling, 2023)
Independence is the ability to control oneself to deal with situations around them without depending on others. Consequently, appropriate parenting styles are necessary to train independence in children, especially children with special needs. This research aims to describe the parenting style of mothers in shaping the independence of children with special needs. This qualitative research used a phenomenological approach. The object of this research was children with special needs aged 12-17 years. While the research subjects were four mothers with children with special needs in the categories of autism, mental retardation, deafness, and ADHD. Data collection methods used structured interviews conducted in-depth with the research subjects. Subsequently, the data analysis used content analysis techniques. The results showed that the mother's parenting pattern of the four subjects in the formation of independence in children with special needs was through democratic parenting. The democratic parenting pattern is characterized by the provision of direction and guidance from parents, especially mothers, in developing children's independence abilities.